2016
DOI: 10.1111/jbi.12868
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation in the marbled white butterfly species complex driven by multiple evolutionary forces

Abstract: Aim Genetic and phenotypic data may show convergent or contrasting spatial patterns. Discrepancies between markers may develop in response to different evolutionary forces. In this study we analyse inter-and intraspecific differentiation of closely related taxa in the marbled white butterfly species group. Based on genetic and phenotypic characters we test for potential evolutionary drivers and propose a taxonomic revision.Location Western Palaearctic (including north-western Africa).Methods We compared distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 43 publications
(65 reference statements)
0
25
0
Order By: Relevance
“…In recent years, several studies that DNA‐barcoded the butterfly species occurring in the Mediterranean and in other regions of Europe highlighted the presence of deep mitochondrial lineages within generally accepted species, suggesting ongoing differentiation or even the presence of cryptic species (Dincă, Dapporto, & Vila, 2011; Dincă, Lukhtanov, & Talavera, 2011; Dincă et al, 2015; Dincă, Zakharov, Hebert, & Vila, 2011; Hausmann et al, 2011). Some of these cases have been subsequently studied in more detail by using integrative approaches and occasionally revealed that species diversity is higher than expected even in intensively studied areas such as Europe (Dapporto, Vodă, Dincă, & Vila, 2014; Dincă, Zakharov, et al, 2011; Habel et al, 2017; Hernández‐Roldán et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies that DNA‐barcoded the butterfly species occurring in the Mediterranean and in other regions of Europe highlighted the presence of deep mitochondrial lineages within generally accepted species, suggesting ongoing differentiation or even the presence of cryptic species (Dincă, Dapporto, & Vila, 2011; Dincă, Lukhtanov, & Talavera, 2011; Dincă et al, 2015; Dincă, Zakharov, Hebert, & Vila, 2011; Hausmann et al, 2011). Some of these cases have been subsequently studied in more detail by using integrative approaches and occasionally revealed that species diversity is higher than expected even in intensively studied areas such as Europe (Dapporto, Vodă, Dincă, & Vila, 2014; Dincă, Zakharov, et al, 2011; Habel et al, 2017; Hernández‐Roldán et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study on Melanargia showed that some taxa of this genus differentiated at the species level possess very low divergence at COI (Habel et al. ). From this perspective, in‐depth analyses of multiple genetic and morphological markers are needed to test the potential existence of cryptic species within M. russiae .…”
Section: Discussionmentioning
confidence: 99%
“…Such loss may be particularly relevant in a genus in which small levels of COI diversification can correspond to high overall diversification (Habel et al. ). These findings also emphasize the value of museum collections which, in combination with continuously advancing DNA techniques, can reveal past genetic diversity with important implications for fields such as phylogeography, taxonomy, and conservation (Strutzenberger et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Habel et al . () combined morphological data with genetically informed phylogeographical methods to evaluate the divergence in the marbled butterfly species group in the Western Palaearctic. The documentation of the phylogeographical patterns in starfish in the Atlantic and Mediterranean Pérez‐Portela et al .…”
mentioning
confidence: 99%